The Relationship Between Spiritual Care Needs and Death Anxiety in Turkish Patients with Chronic Obstructive Pulmonary Disease - Yıldız, Ezgi (Journal of religion and health, 2025)
This study aimed to determine the levels of spiritual care needs and death anxiety, as well as the relationship between them, in Turkish patients with chronic obstructive pulmonary disease (COPD). This descriptive and correlational study included 480 patients who were admitted to the pulmonology outpatient clinics of a public hospital with a diagnosis of COPD between November 1, 2023, and April 31, 2024. The study data were collected using the Patient Diagnosis Form, Dyspnea Fear Level Assessment Form, Spiritual Care Needs Inventory, and Templer Death Anxiety Scale. It was determined that 60.8% of the patients had high death anxiety and moderate spiritual care needs. A positive correlation (r = 0.327; p < 0.01) was found between the mean scores of the Spiritual Care Needs Inventory and the Templer Death Anxiety Scale. Patients with high death anxiety also had high spiritual care needs (p < 0.01). It was determined that the gender of the patients, fear of dyspnea, and death anxiety predicted 20% of the need for spiritual care (R = 0.457, R2 = 0.209, F = 17.800, p < 0.001). Considering the study findings, it can be stated that death anxiety may decrease as the spiritual needs of the patients are met. Within the framework of holistic care, it is essential for health professionals to identify patients' spiritual needs in addition to their physical and psychological needs and to implement interventions to meet these needs.